Political Dissatisfactions and Citizen Involvement: Political Participation in Europe during the Early Stages of the Economic Crisis - Christensen, Herink Serup (PARTECIPAZIONE E CONFLITTO, 2016)
This article examines the links between three kinds of political dissatisfaction and four types of political participation during the early stages of the economic crisis in 2008-2009. Since economic crisis exacerbates negative political attitudes and thereby strains the legitimacy of the political system, it is im-portant to examine how citizens convey their grievances to political decision makers during such crisis. Recent decades have witnessed changes in patterns of political participation entailing that citizens abstain from traditional political participation in favor of non-institutionalized activities, but the implications for democracy are disputed since it is unclear what drives non-institutionalized participation. To ascertain what the changes mean for democracy during times of economic crisis, it is helpful to distinguish different kinds of political dissatisfaction with diverse implications for democracy. The data comes from the fourth round of the European Social Survey and include a total of 47489 respondents in 25 European democracies. The results suggest that only some kinds of political dissatisfaction affect the pro-pensity for political participation while others lead to passivity. Additionally, political dissatisfaction is not necessarily a major driving force behind the popularity of non-institutionalized participation since satisfied citizens are also involved in these.